Analysis of Sesamum indicum Seed Oil from Plants Grown in Flyash Amended Acidic Soil - Thetwar, L.K.; Prasad Sahu, Dhaneshwar; Murari Vaishnava, Madan; Kumar Soni, Kiran; Khokhar, M.S.K. (Asian Journal of Chemistry, 2010)
In the present work, flyash amended acidic soil along with plant hormones like gibberellic acid and indole acetic acid were used to increase crop yield and oil-contents, avoiding the aluminium ion toxicity, which might have affected the quality and the medicinal values of sesame seed oil. The seed and oil quality parameters from plants grown in plain and flyash, hormone treated soils were compared after pot experiments.